2016
DOI: 10.1039/c6ra01310d
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the breakthrough curves of VOC isothermal adsorption on hypercrosslinked polymeric adsorbents in a fixed bed

Abstract: The new method established in this paper has good accuracy for predicting the adsorption capacity and breakthrough curve without requiring experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Because of the high consistency between the experimental and predicted data, it is possible to utilize the proposed model to analyze the breakthrough time. [ 19 ] The calculated breakthrough times for the adsorption of o ‐xylene, benzene, and acetone onto CNSL‐HCP4 were 200, 37, and 18 s, respectively. The breakthrough time of o ‐xylene vapors among these vapors was the longest, and contrarily the breakthrough time of acetone vapors was the shortest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the high consistency between the experimental and predicted data, it is possible to utilize the proposed model to analyze the breakthrough time. [ 19 ] The calculated breakthrough times for the adsorption of o ‐xylene, benzene, and acetone onto CNSL‐HCP4 were 200, 37, and 18 s, respectively. The breakthrough time of o ‐xylene vapors among these vapors was the longest, and contrarily the breakthrough time of acetone vapors was the shortest.…”
Section: Resultsmentioning
confidence: 99%
“…[15] Recently, Long and other group members have demonstrated that hypercrosslinked polymeric resins have excellent adsorption properties for some VOCs, such as the vapors of chlorides, ketones, alkanes, gasoline, monocyclic aromatics, and esters. [16][17][18][19][20][21] Wang's group synthesized hypercrosslinked polymers (HCPs) with polydivinylbenzene as raw material and their dynamic adsorption results showed high adsorption amount of benzene (137 mgÁg À1 ), which was obtained under certain humidity conditions. [22] Also, Wang and other workers reported an analogous adsorbent prepared by an external cross-linker knitting method.…”
mentioning
confidence: 99%
“…Further work was done by Yi et al [22], Ebrahimi. et al [23], Xiu [24], and Wu et al [25], who mainly based their models on equations for linear driving force and thin film diffusion [26,27] at low solute concentrations [28]. All of the above were typical models for predicting breakthrough curves, which provided some inspiration for this work.…”
Section: Introductionmentioning
confidence: 97%
“…There are few studies that have attempted to model ion exchange using a finite difference method. Yi [22] and Jian Wu [25] used a finite difference method to solve an ion exchange model, and the difference compared to this work was that the complete derivation and discretization of the difference equation. The results of their work produced comprehensive computational data.…”
Section: Introductionmentioning
confidence: 99%